1996
DOI: 10.1071/rd9960409
|View full text |Cite
|
Sign up to set email alerts
|

Liquid ventilation in premature lambs: uptake, biodistribution and elimination of perfluorodecalin liquid

Abstract: Perfluorochemical (PFC) liquids are biologically inert and nonbiotransformable substances that, when used as breathing medium, may be transported across the lung epithelium in small quantities, distributed throughout the body, and ultimately vapourized through the lungs and transpired through the skin. To further evaluate the uptake, biodistribution and elimination of a PFC liquid (perfluorodecalin) in the neonatal population, arterial blood, tissue and expired gas samples were obtained from preterm lambs (105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 21 publications
0
36
1
2
Order By: Relevance
“…Small amounts of PFC are detected in the blood of liquid-ventilated animals. 28 Uptake of PFC by other tissues is dependent on its blood flow and fat content, with highest levels (apart from the lungs) found in fat, brain and intestine. 28 Probably minuscule amounts are transpired through the skin.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of PFC are detected in the blood of liquid-ventilated animals. 28 Uptake of PFC by other tissues is dependent on its blood flow and fat content, with highest levels (apart from the lungs) found in fat, brain and intestine. 28 Probably minuscule amounts are transpired through the skin.…”
Section: Animal Studiesmentioning
confidence: 99%
“…28 Uptake of PFC by other tissues is dependent on its blood flow and fat content, with highest levels (apart from the lungs) found in fat, brain and intestine. 28 Probably minuscule amounts are transpired through the skin. There is also an uptake of PFC by macrophages in the lung, liver and spleen.…”
Section: Animal Studiesmentioning
confidence: 99%
“…PFC-administered as liquid (11), vapor (12), or gas (13) into the lung-represent an alternative approach to treat respiratory insufficiency. Intratracheal PFC application prolonged the survival of rats with bacterial pneumonia (14) and reduced the bacterial count in the lungs of newborn rabbits with connatal group B streptococcal pneumonia (15).…”
mentioning
confidence: 99%
“…It has been employed for whereas no signal was detected from the pancreatic segment. This indicates that any PFC present in the tissue detection of trace amounts of PFC in blood and tissues of premature lambs during liquid ventilation experiwas below the detection limit of the MR experiment as no fluorine signal could be obtained from the pancreas ments (30). The authors concluded that following uptake of trace amounts (of the order of nl/g of tissue), PFC from a series of volumes of 0.25 mm 3 .…”
Section: Linearity and Precisionmentioning
confidence: 99%